Pain prevalence, characteristics and associated factors in human T-cell lymphotropic virus type 1 infected patients: a systematic review of the literature - San-Martin,Daniel Lordelo (2016)
ABSTRACT Objective: To describe the pain in patients infected with human T-cell lymphotropic virus type 1, clinically and epidemiologically. Methods: This systematic review was based on The PRISMA Statement. Four reviewers searched PUBMED, SciELO, LILACS and BIREME for data from observational studies and clinical trials (n ≥ 30) regarding pain prevalence, characteristics, and associated factors in patients with human T-cell lymphotropic virus type 1. No limits on publication date or language were established. Studies that did not have pain as an outcome measure or not involving human T-cell lymphotropic virus type 1 infected patients were excluded. Results: A total of 3013 articles (including duplicates) were found of which seven met the predetermined criteria. The most common pain region was the lower back (53.0%). Non-neuropathic type (ranging from 52.6% to 86.8%) was more frequent in human T-cell lymphotropic virus type 1-associated myelopathy/tropical spastic paraparesis participants, and neuropathic pain was more common in human T-cell lymphotropic virus type 1 carriers (53.1%). The pain was mostly reported as moderate or severe. One study showed that chronic pain was negatively associated with quality of life. Discussion: Pain is a common complaint in human T-cell lymphotropic virus type 1 infected patients, with lower back pain as the most frequent site. Pain can either be nociceptive, neuropathic, or both, is frequently severe, and negatively affects quality of life. Only studies of two countries were included in this review, limiting the external validity of the conclusions. The heterogeneity of variables prevented us from implementing a meta-analysis. Further research should better characterize the pain and explore its impact on quality of life, especially using longitudinal study design.